2008
DOI: 10.1186/1550-2783-5-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and 14-day coenzyme Q10 supplementation on exercise performance in both trained and untrained individuals

Abstract: Background: To determine whether acute (single dose) and/or chronic (14-days) supplementation of CoQ10 will improve anaerobic and/or aerobic exercise performance by increasing plasma and muscle CoQ10 concentrations within trained and untrained individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 42 publications
8
79
0
8
Order By: Relevance
“…In another study, serum MDA levels were also unaffected by treatment of CoQ 10 in trained cyclists (46). On the contrary, Cooke et al (47) stated that acute supplementation with CoQ 10 resulted in higher MDA levels during and following exercise. They indicated that acute and chronic supplementation of CoQ 10 may affect acute and/or chronic responses to various types of exercise.…”
Section: Discussionmentioning
confidence: 92%
“…In another study, serum MDA levels were also unaffected by treatment of CoQ 10 in trained cyclists (46). On the contrary, Cooke et al (47) stated that acute supplementation with CoQ 10 resulted in higher MDA levels during and following exercise. They indicated that acute and chronic supplementation of CoQ 10 may affect acute and/or chronic responses to various types of exercise.…”
Section: Discussionmentioning
confidence: 92%
“…This fold increase resulted in increased CoQ10 in heart (11.3%), breast (45%), wings (25%) and legs (16%) of chicken. Cooke et al (2008) and Gopi et al (2014a) recorded an increase in muscle CoQ10 at 20 mg kgG 1 content with reduction in muscle cholesterol content but were not at 40 mg of CoQ10 kgG 1 of diet. Krizman et al (2012) also proposed that for production of functional food chicken, supplementation of CoQ10 could be considered in future as CoQ10 in Asian J.…”
Section: Coenzyme Q10 Absorption Among Body Tissuesmentioning
confidence: 99%
“…Acute and chronic supplementation of CoQ 10 may affect acute and/or chronic responses to various types of exercise [85,88]. CoQ 10 supplementation increased total CoQ concentration in the slow-twitch muscles and was useful for reducing exhaustive exercise-induced muscular injury by enhancing stabilization of muscle cell membrane [89].…”
Section: Ubiquinonesmentioning
confidence: 99%